Daniele Rossi, Realtà virtuale: disegno e design, Aracne editrice, Canterano (Roma) 2020 (diségno, 2021)
Daniele Rossi’s book, entitled Realtà virtuale: disegno e design, tackles a highly topical issue. The methodology of virtualization of reality perceived through an HMD (Head-Mounted Display) system, i.e. a device equipped with a stereoscopic optical system for the dynamic fruition of a digital scene, is reaching its full maturity. [read more]